2016
DOI: 10.1007/s00210-016-1281-z
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and genotoxic evaluation of rosmarinic and caffeic acid in acute seizure models induced by pentylenetetrazole and pilocarpine in mice

Abstract: The goal of this study was to investigate the effects of rosmarinic acid (RA) and caffeic acid (CA) in the acute pentylenetetrazole (PTZ) and pilocarpine (PIL) seizure models. We also evaluated the effect of RA and CA on the diazepam (DZP)-induced sleeping time test and its possible neuroprotective effect against the genotoxic damage induced by PTZ and PIL. Mice were treated intraperitoneally (i.p.) with saline, RA (2 or 4 mg/kg), or CA (4 or 8 mg/kg) alone or associated to low-dose DZP. After, mice received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
7
0
2
Order By: Relevance
“…To put it simply, the ICT complex and its components are not genotoxic under the stated experimental conditions. CA is a well-known antioxidant with a strong reducing ability, 43 and, in addition, it did not exhibit genotoxicity in the comet assay experiments using concentrations that exceed the highest concentration in this study. However, the genotoxicity of TiO 2 NPs is still a matter of debate in the literature.…”
Section: Combinatorial Effect On Genotoxic and Antigenotoxic Properties Of The Ict Complex And Its Componentsmentioning
confidence: 50%
See 1 more Smart Citation
“…To put it simply, the ICT complex and its components are not genotoxic under the stated experimental conditions. CA is a well-known antioxidant with a strong reducing ability, 43 and, in addition, it did not exhibit genotoxicity in the comet assay experiments using concentrations that exceed the highest concentration in this study. However, the genotoxicity of TiO 2 NPs is still a matter of debate in the literature.…”
Section: Combinatorial Effect On Genotoxic and Antigenotoxic Properties Of The Ict Complex And Its Componentsmentioning
confidence: 50%
“…These results are in agreement with published data concerning the antigenotoxic effect of unmodified TiO 2 NPs, 22 and antigenotoxic effect of CA. 43 Post-treatment with the ICT complex formed between TiO 2 and CA displayed antigenotoxic effect at lower concentrations (0.5-1.6 mg mL -1 ICT; mole ratio c(TiO 2 )/c(CA) = 8). However, at higher concentrations (>5 mg mL -1 ICT; mole ratio c(TiO 2 )/c(CA) = 8), the ICT complex showed no beneficial effect on H 2 O 2 damaged cells.…”
Section: Combinatorial Effect On Genotoxic and Antigenotoxic Properties Of The Ict Complex And Its Componentsmentioning
confidence: 93%
“…In a study cited by revealed that polyphenols such as ferulic acid possess neuroprotective effects against oxidative and inflammatory stress. [35][36][37][38] Besides, in the study conducted by Li et al, revealed that berberine strongly attenuates the toxic effects of oxidative and inflammatory stress by amelioration of SOD and reduction of NOS oxidative enzyme, MAPKs and interleukins. [39]…”
Section: Discussionmentioning
confidence: 99%
“…All drugs were dissolved in saline (NaCl 0.9%) solution. The doses of LCM and DZP were chosen based on previous studies [14–17]. The PTZ dose used was 50 mg/kg s.c., obtained through a pilot test.…”
Section: Methodsmentioning
confidence: 99%
“…The study design is summarized in Figure . Animals were given intraperitoneal injections of saline and DZP (2 mg/kg), 30 min before the subconvulsive stimuli (PTZ 50 mg/kg, s.c.) according to Coelho et al [17,19]. LCM (20, 30, and 40 mg/kg) was administered by gavage one hour before subconvulsive stimuli so that the plasmatic concentration of drug was adequate [13].…”
Section: Methodsmentioning
confidence: 99%